COVID-19-related factors affecting construction labour productivity in Zimbabwe - Benviolent Chigara; Tirivavi Moyo (Journal of Construction Project Management and Innovation)
The COVID-19 pandemic aggravated the underlying productivity challenges in the construction sector. However, not much is known regarding how the pandemic affected labour productivity in developing countries such as Zimbabwe. Therefore, this study investigates the COVID-19-related factors affecting construction labour productivity in Zimbabwe. A survey design entailed the distribution of an online questionnaire to construction professionals in Bulawayo and Harare. The data was analyzed using descriptive statistics. Factor analysis was also utilized to reveal significant factors affecting construction labour productivity. Factor analysis revealed nine (9) significant factors contributing to reduced labour productivity during the COVID-19 pandemic, namely: poor project planning and management issues; permits and inspection delays; cash flow and payment challenges; compliance with COVID-19 health and safety (H&S) protocols; disruption of project activities; lack of empowerment and capacity building; material supply disruptions; labour supply disruptions; and design changes and poor information transfer. Construction stakeholders can use the results of this study to design appropriate interventions to prevent/reduce pandemic-related productivity losses. However, differences in insights due to demographic variables were not determined to enable targeted interventions. This study is among the emerging studies investigating how the COVID-19 pandemic affected construction labour productivity from a developing country perspective, with the consequent determination of appropriate interventions envisaged.